Pengaruh Profitabilitas, Ukuran Perusahaan,Dan Kinerja Lingkungan TerhadapPengungkapan Islamic Social Reporting (ISR)(Studi Empiris Pada Perusahaan Yang Terdaftar Di Daftar Efek Syariah Tahun 2015) - , Widarto; , Drs. Agus Endro Suwarno, M.Si (2017)
Islamic Social Reporting (ISR) is an extension of social performance reporting standards which include society's expectations not only about the company's role in the economy, but also the company's role in the spiritual perspective. ISR index contains six (6) themes, namely: investment and finance, products and services, employees, communities, the environment and corporate governance. The purpose of this study was to test the effect of profitability, company size, and environmental performance on the disclosure of Islamic Social Reporting. The population in this study are all companies listed in the Daftar Efek Syariah (DES) during two periods in 2015. The number of samples tested by 44 companies selected by purposive sampling method. This research analyze the company's annual report with content analysis. Technique analysis of this study using descriptive analysis and statistical analysis. The results showed that the profitability of a significant effect on the disclosure of Islamic Social Reporting, company size has no significant effect on the disclosure of Islamic Social Reporting. Then the environmental performance also had no significant effect on the disclosure of Islamic Social Reporting.